Enhancing Pedagogical Competence : Evaluating Islamic Religious Education Practices in West Aceh - Suharman, Suharman (STAI Hubbulwathan Duri, 2024)
The research aims to explore teachers' pedagogical competence in implementing evaluations of Islamic religious education, preparation for evaluations, use of information technology in implementing evaluations, implementation of comprehensive evaluations, and implementation of differentiated evaluations. Data collection methods included observations, interviews, and documentation. The selection of respondents employed purposive sampling to ensure data accuracy by directly sourcing primary information. Respondents consisted of school principals, school operators, and Islamic education teachers from high schools in the Aceh Barat region. Six tests were utilized to ensure data credibility: extension of observation time, triangulation, member checking, independent analysis, theoretical validity, and negative case analysis. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing or verification. The research results show that teachers' pedagogical competence in implementing Islamic religious education evaluations is quite good, with several innovations being made. These innovations include comprehensive evaluation approaches, student potential-oriented assessments, the utilization of observational results from the learning process, and the use of information technology to enhance the accessibility of the evaluation process. Further research is recommended on the application of evaluation guidelines in the affective and psychomotor domains within Islamic education at the high school level to complement the findings of this study.